The Role of Habit and Trust in Driving the Continuance of QR Code Payment Usage: A Study of QRIS Consumers in Indonesia - Wicaksono, Imam (Politeknik Negeri Bandung, 2025)
Sustaining the ongoing use of digital payment systems is a key challenge in financial innovation. This research tackles the problem by examining the factors that influence the continuance intention of the Quick Response Code Indonesian Standard (QRIS), expanding the Technology Continuance Theory (TCT) through the inclusion of trust and habit as mediating factors. Employing a quantitative methodology with a non-probability purposive sampling technique, data were collected from 938 active QRIS users and analyzed using PLS-SEM. The results demonstrate that confirmation, perceived ease of use, and satisfaction significantly cultivate trust and habit. These constructs, in turn, function as essential mediators, with habits being the principal predictor of users' continuance intention. Notably, perceived usefulness and price benefits did not exhibit a strong direct effect. This study offers two main implications. From a theoretical perspective, it enhances post-adoption models by emphasizing the significant mediating effects of trust and habit. From a practical standpoint, it recommends that providers prioritize cultivating user trust and encouraging habitual use to support long-term adoption, rather than depending solely on functional features.